Perbedaan intensitas prososial siswa SMUN dan MAN di Yogyakarta - Alfi Purnamasari; Endang Ekowarni; Avin Fadhila (HUMANITAS: Indonesian Psychological Journal, 2004)
The purpose of this study is to find out the differences of prosocial intention between students of Sekolah Menengah Umum Negeri (SMUN) and students of Madrasah Aliyah Negeri (MAN) in Yogyakarta, between male students and female students in general, and between female studets and male students in each school. The total subjects of the research were 214 students of Sekolah Menengah Umum Negeri 6 (SMUN 6) and Madrasah Aliyah Negeri I (MAN I) Yogyakarta. The students of SMUN 6 consisted of 42 Female sudents and 61 male students, while the students of MAN I consisted of 49 female students and 62 male students. Prosocial Intention Scale was used as data collecting method.Â The results show that there is no difference of prosocial behavior between the students of SMUN and the students of MAN (F=1.116, p>0.05, SMUN average 98.86, MAN average 97.73), there is no differences of prosocial behavior between female students and male students in general (F=1.077;p>0.05; the female students average 98.79, the male students average 97.76), there is no differences of prosocial behavior between male students of SMUN and MAN (t=0.380;p>0.05; the male students of SMUN average 97.35, the male students of MAN average 98.05), there is no differences of prosocial behavior between female students of SMUN and MAN (=-1.870: p>0.05; the female students of SMUN average 100.05 and the female students of MAN 97.51).